PERILAKU MEMILIH MASYARAKAT KEPENGHULUAN SUNGAI SEGAJAH MAKMUR PADA PEMILUKADA TAHUN 2015 - Julia Hafizatun Nisyak; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to determine the voting behavior segajah river communities prosper in the election in 2015. The study focused on the defeat H.Suyatno the majority ethnic community of Java, while H.Suyatno ethnic Javanese. With the formulation of research problems, namely how to choose the behavior of society segajah river affluent in the election in 2015. Based on the background of the problem, the study aims to identify and analyze the voting behavior of society kepenghuluan segajah river affluent districts downstream rokan 2015. The research method is quantitative, with the type of Causal comparative studies and then using the sample population. Data was collected by questionnaire, and documentation. The results of the field studies showed that the voting behavior segajah river affluent society kepenghuluan not use mashab sociological, but using a psychological approach and the economic approach. it is seen from the answers to questionnaires from the public kepenghuluan segajah river that ethnic Javanese. based on research by the author H.Suyatno the Java tribes lost in the river kepenghuluan segajah prosperous, while the reason the majority of people do not choose H.Suyatno namely because of disappointment, people are not familiar with H.Suyatno, Peoples followed increments families, communities want to change, and H .Suyatno less sociable with people kepenghuluan segajah prosperous river. In this study the authors concluded that the sociological mashab not affect the voting behavior of the river kepenghuluan segajah prosperous society in 2015, but the community kepenghuluan segajah river mashab prosperous using psychological and economic mashab in selecting candidates for the heads of districts rokan downstream. Keywords: Behavior Choosing, Election